Immobilization and detection of platelet-derived extracellular vesicles on functionalized silicon substrate: cytometric and spectrometric approach - Gajos, Katarzyna (Anal Bioanal Chem, 2016)
Among the various biomarkers that are used to diagnose or monitor disease, extracellular vesicles (EVs) represent one of the most promising targets in the development of new therapeutic strategies and the application of new diagnostic methods. The detection of circulating platelet-derived microvesicles (PMVs) is a considerable challenge for laboratory diagnostics, especially in the preliminary phase of a disease. In this study, we present a multistep approach to immobilizing and detecting PMVs in biological samples (microvesicles generated from activated platelets and human platelet-poor plasma) on functionalized silicon substrate. We describe the application of time-of-flight secondary ion mass spectrometry (TOF-SIMS) and spectroscopic ellipsometry methods to the detection of immobilized PMVs in the context of a novel imaging flow cytometry (ISX) technique and atomic force microscopy (AFM). This novel approach allowed us to confirm the presence of the abundant microvesicle phospholipids phosphatidylserine (PS) and phosphatidylethanolamine (PE) on a surface with immobilized PMVs. Phosphatidylcholine groups (C(5)H(12)N(+); C(5)H(15)PNO(4) (+)) were also detected. Moreover, we were able to show that ellipsometry permitted the immobilization of PMVs on a functionalized surface to be evaluated. The sensitivity of the ISX technique depends on the size and refractive index of the analyzed microvesicles. [Figure: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00216-016-0036-5) contains supplementary material, which is available to authorized users.